2022
DOI: 10.1039/d1re00396h
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the reactivity of single atom alloys for ethanol dehydrogenation using ab initio simulations

Abstract: An ab initio micro-kinetic model (MKM) is constructed to understand the reactivity trend of single atom alloys (SAAs) of Cu and Au for non-oxidative dehydrogenation (NODH) of ethanol to produce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
(119 reference statements)
1
11
0
Order By: Relevance
“…Since d‐band center alone is not expected to form a credible descriptor for the SAAs formed from the group 11 elements, other features from the periodic properties of the elements are included in the model. The test errors for E O and E C , estimated from the ML model are around 0.2 eV (Figure 5(a) and (b)), which is similar to the error bars on DFT calculations reported in our earlier studies [7,36,64–67] . Toyao et.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Since d‐band center alone is not expected to form a credible descriptor for the SAAs formed from the group 11 elements, other features from the periodic properties of the elements are included in the model. The test errors for E O and E C , estimated from the ML model are around 0.2 eV (Figure 5(a) and (b)), which is similar to the error bars on DFT calculations reported in our earlier studies [7,36,64–67] . Toyao et.…”
Section: Discussionsupporting
confidence: 88%
“…[19] Finally, the efficacy of the ML model is tested for the NODH reaction of ethanol, using E O and E C as descriptors using a previously built ab initio MKM for the estimation of turnovers of ethanol consumption on metal catalysts. [36] The ML model has predicted significantly higher TOFs for the NiAu SAA as compared to the Au surface (Figure 9(b)), with the difference of four order of magnitude. The result is consistent with the experimental study undertaken by Giannakakis et al wherein they observed a decrease in the apparent activation energy of NiAu as compared to pure Au catalyst towards the NODH of ethanol, thus indicating higher production rates over the SAA.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations